The skills of reading aloud and critically for fifth grade preparatory students, types and mastery (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify the extent to which the fifth preparatory grade students master the skills of reading aloud and the skills of critical reading.To achieve the goal of the research, the researcher randomly selected Al-Tahrir School, Al-Maymoon School for Boys, and That Al-Nitaqain School for Girls from among the preparatory day schools affiliated to the Directorate of Education in Wasit Governorate, to be a field for the application of the research.